How Can Theological Ethics Be Christian? - Ottati, Douglas F. 1950- (2011)
THIS ESSAY PRESENTS THE ARGUMENT THAT A THEOLOGICAL ETHIC CAN be Christian if it is shaped by a Christian theology or a reflective attempt to articulate a Christian worldview in the service of the life of faith. But there is no generic Christian theology, only historical varieties, many of which shape our ethics differently and also include distinctive self-critical resources. Therefore, although theology is not all you need, you must also be your own theologian to be a critical, interesting, and ecclesially relevant Christian ethicist.